The Use of Social Media at State Islamic Colleges - Muhammad Munadi (Tadbir : Jurnal Studi Manajemen Pendidikan, 2021)
This study aims to determine the management of social media, the trend of followers of each social media, as well as the use of social media in universities under the Ministry of Religion Affairs, especially in the area of the island of Java. This study used content analysis research with data derived from the website, documents that can be downloaded from the website relating to social media university activities and its development. Social media used as research are all types of social media used by IAIN Ponorogo, IAIN Surakarta, IAIN Kudus, IAIN Pekalongan, IAIN Salatiga, UIN Walisongo Semarang, and IAIN Ponorogo. Data analysis used interactive analysis and descriptive statistical analysis. The results showed that the management of social media is in the Public Relations and Publications sub-section of each PTKI with one admin operating on each social media made. the most followers on Instagram social media are IAIN Salatiga. For social media youtube is IAIN Ponorogo, while the most Twitter follower IAIN Surakarta and Facebook followers the most is IAIN Pekalongan. The use of diverse social media, on Instagram for academic activities including promotion for prospective new students dominant in all research locations and balanced with greeting content of national and religious activities by 83.3%, for YouTube by 66.6% dominant content of academic activities and this is the same as what happened to the Twitter, while on social media Facebook a percentage of 66. 6% in the content of academic activities and balanced with the greeting content of national and religious activities. The development of social media content lies in quoting national and religious activities Utilization of social media can be used for all higher education service activities within the scope of the tri dharma of higher education, both the dharma of education/teaching, research, and community service.